STRATEGI DIFERENSIASI UNTUK MEMPEROLEH KEUNGGULAN BERSAING PADA HOTEL BERBINTANG DI SURAKARTA - Luluk Takari Sarjana Rini; Sri Hutami (STIE Atma Bhakti, 2017)
In recent years the hospitality industry in Surakarta has been rapidly increasing. The number of star hotels jumped from 19 in 2010 to 34 in 2013, and in 2016 to 57 star hotels. The increase has not been matched by the growing number of tourists staying at star-rated hotels, but decreased by 5% over the same period. This condition requires the management to be able to manage well in order to avoid bankruptcy. This study was conducted to test whether there is a difference between the implementation of differentiation strategy between 2 and 3 star hotels that have long standing with new hotels to competitive advantage to win the competition, by using dependent variable: price, service quality, promotion, size and location and independent variable: competitive advantage. To test it using Independent Sample T-test. The result of the research shows that there is no difference in the implementation of price differentiation strategy, service quality, promotion, size and location to get competitive advantage between 2 and 3 star hotels that have long standing with new hotel. This condition will make the customer not stay in certain hotels or customers are not fanatical towards a particular hotel, thus allowing customers to move from one hotel to another hotel to try without feeling any difference / value more than any other hotel they have ever used before to spend the night, so the hotel will only be able to achieve the profits of a standard profit economy only. Based on the above conclusions, hotel management is required to be able to choose the right strategy by developing its competitive advantage based on its own internal resources and management activities to maintain its existence in order to continue to grow and win the competition. Keywords: Differentiation Strategy, Competitive Advantage, Hotel